“Os brancos não falam a verdade contra mim. Porque ele é homem e não havia de passar o trabalho que as fêmeas passam”: Maria Rita e a interseccionalidade na experiência de mulheres escravizadas (Comarca de Rio Pardo, século XIX) - Santos, Bruna Letícia de Oliveira dos (Universidade do Vale do Rio dos Sinos, 2020)
The writing of this dissertation had the drive to question how gender is socially built for black women and how it was lived by these same women in History. We search to construct answers from analysis of criminal processes that involved enslaved black women at the county of Rio Pardo, state of Rio Grande do Sul, during the XIXth century through the relationship between gender, race, and judicial condition of enslaved women. In the gathering of sources and in the process of structuration of the research, the experience of Maria Rita - a black minanagô who lived her motherhood as a black woman under the judicial status of slavery – became the main focus of our historical inquiry. Maria Rita presented us with the intersections of the place that a woman had in that slave society. For many times, she was the mediator between two worlds, the enslaved and the one that did not recognize the impositions of slavery because of her African origin. Still, intersectionality was the key element across this study and was used in the analysis through different perspectives. Initially, we used it as a methodological tool to think about black women in historiographical researches. In this sense, the intersection between gender, race, and judicial condition has presented black women as an analytical category in the gender studies about slavery. Yet, with the focus of analysis in women, we perceive intersectionality as a living experience in a History bounded by the structure of slavery domination that exploited black women as enslaved workers that were constituted by the racialization of gender as the intersectional cornerstone of the system. And, by the movement and actions of women in the sense of preservation, the recreating and continuity of the humankind.
Keywords: Interseccionalidade; Experiência; Gênero racializado; Mulheres negras; Maternidade; Intersectionality; Experience; Gender-racialized; Black women; Motherhood; ACCNPQ::Ciências Humanas::História